PENGUASAAN PENYUSUNAN MODUL AJAR GURU PPKn DI SMP NEGERI 3 GALESONG SELATAN KABUPATEN TAKALAR - Bachtiar, Nuraeni; Haris, Hasnawi; Mustari, Mustari (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2025)
Abstract: This study aims to find out, (1) the ability of PPKn teachers at SMP Negeri 3 South Galesong in compiling teaching modules in accordance with the Independent Curriculum, (2) the obstacles faced by PPKn teachers at SMP Negeri 3 Galesong Selatan in compiling teaching modules in accordance with the Independent Curriculum, (3) the efforts made by PPKn teachers at SMP Negeri 3 South Galesong in compiling teaching modules in accordance with the Independent Curriculum. This study uses a qualitative method with a descriptive approach, while the data collection procedures used are interviews, observations, and documentation. The results of the study show that (1) Teachers have the ability to compile teaching modules based on the Independent Curriculum at a